The social dimension of modern media space and its content - V L Mouzykant; P V Mouzykant (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The article describes the nature of the relationships between subjects of the modern media space as a part of an open social system. The authors analyze the consequences of growth of media consumption, the Internet influence on the behavior of Russians and methods to measure the emerging media space and social networks.